Standardization of Buffers and Substrate Solutions for in-vivo Nitrate Reductase Activity in Cinnamomum camphora (L.) J.Presl Leaves - Sengar, Meenu Singh; Chaukiyal, S. P.; Sharma, Priyanshu (Indian Forester, 2016)
The assessment of in-vivo nitrate reductase (NR) activity in leaves of Cinnamomum camphora was performed to obtain the most suitable substrate and phosphate buffer solutions for the estimation of maximum in-vivo NR activity. Phosphate buffer (0.1M and 0.2M) solution with pH ranging from 7.0 to 7.8 and concentration of substrate (KNO3) solution varying from 0.05, 0.10, 0.15, 0.20 and 0.25M were used in the present experiment. Highest nitrate reductase activity was recorded in the combination of phosphate buffer 0.2M solution having pH 7.2 and substrate solution of the concentration 0.15M.